2016
DOI: 10.3892/or.2016.5162
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phycoerythrin from Gracilaria lemaneiformis in proliferation and apoptosis of SW480 cells

Abstract: We studied phycoerythrin (PE) in human SW480 tumor cells and the underlying molecular mechanisms of action. PE inhibited cell proliferation as evidenced by CCK-8 assay. The IC50 values of phycoerythrin were 48.2 and 27.4 µg/ml for 24 and 48 h of exposure, respectively. PE induced apoptosis and cell cycle arrest in SW480 cells as observed under electron microscopy and with flow cytometry. Apoptosis increased from 5.1 (controls) to 39.0% in 80.0 µg/ml PE-treated cells. Differences in protein expression were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…Phycoerythrin (PE) is a bioactive pigment mainly found in Rhodophyta, but it can also be recovered from Cyanobacteria [1]. This water-soluble pigment is a bioactive molecule with interesting properties such as anti-inflammatory, immunosuppressive, antitumor, antioxidant, antidiabetic, and antihypertensive effects [2,3,4,5]. In addition, PE moiety can be exploited as a fluorescent probe useful in cell tracking and imaging assays such as flow cytometry, fluorescent immunoassays, and immunophenotyping.…”
Section: Introductionmentioning
confidence: 99%
“…Phycoerythrin (PE) is a bioactive pigment mainly found in Rhodophyta, but it can also be recovered from Cyanobacteria [1]. This water-soluble pigment is a bioactive molecule with interesting properties such as anti-inflammatory, immunosuppressive, antitumor, antioxidant, antidiabetic, and antihypertensive effects [2,3,4,5]. In addition, PE moiety can be exploited as a fluorescent probe useful in cell tracking and imaging assays such as flow cytometry, fluorescent immunoassays, and immunophenotyping.…”
Section: Introductionmentioning
confidence: 99%
“…It was previously shown that variations in the chemical structure of a prebiotic can impact its selective fermentation by bacteria [41]. For this reason, there were published large works regarding the investigation of the potential prebiotic effect of single polysaccharides, often contained in seaweeds, but employing pure standards [42][43][44]. However, it should be considered that seaweeds contain other components than also can affect GM.…”
Section: Polysaccharides From Marine Seaweedsmentioning
confidence: 99%
“…Other important peptides are renin inhibitor tridecapeptide [65] and dipeptide [66], which demonstrated hypotensive effect dipeptide. Phycoerythrin [43] and kahalalide F [67] are other important peptidic compounds isolated from seaweeds than showed antitumor effect.…”
Section: Other Bioactive Compounds From Marine Seaweedsmentioning
confidence: 99%
“…After extensive in vitro studies which demonstrated the cytotoxic activity of phycoerythrin 15 (Figure 3) [94,107], Pan et al [92] demonstrated its activity in vivo using the S180 tumor-bearing mice model ( Table 2). Results showed that phycoerythrin injection, at a dose of 300 mg/kg b.w., reduced S180 tumor growth by up to 41.3% in treated mice.…”
Section: Phycoerythrinmentioning
confidence: 99%